CLEAN PRODUCTION TECHNIQUES IN HANDLING REMAINS AND WASTE COMPONENTS OF FISHERY ACTIVITIES AT KUTARAJA FISHING PORT, ACEH - Putra, Demo Buana; Mustaruddin; Puspito, Gondo; Wiyono, Eko Sri; Baskoro, Mulyono S.; Zulkarnain (Departemen PSP IPB, 2025)
Kutaraja Ocean Fishing Port (OFP) is the center of capture fisheries activities that supplies the largest sea fish in Aceh Province. However, the burden of discarded residual components and waste that was formed tends to increase to disrupt port operations. The study aimed to 1. determine critical activities of waste formation, and 2. develop clean production techniques for handling residual components and waste from fisheries activities at Kutaraja OFP. The research method consisted of a descriptive method, a pollution prevention approach model, and a weighted portion analysis. The critical points for the formation of residual components and waste were fish unloading at pier 1 (old pier), fish auction places 1-3, supply kiosks, and food stalls. Clean production techniques for handling residual components and waste in fish handling were 1. Refine, using freezer cooling technology on ships, and 2. Reduce, reducing rinsing by providing hygienic containers or places for fish. For handling the remaining components and waste scattered in the port were 1. Refine, repair the channels and waste water reservoirs, and 2. Recycle, recycle organic waste into fertilizer that can be used for greening in the Kutaraja OFP area. Keywords: fisheries, fishing industry, ports, residual components, waste